Predicting Bus Operator Retention Based on Employee Characteristics and Work History. Issue 8 (December 2018) - Lind, Eric; Huting, Joel
Turnover of employed bus operators increases cost of service for transit agencies, meaning interventions to reduce turnover can be a common goal. To be effective, interventions should be based on an understanding of the types, timelines, and underlying reasoning for operators separating from employment. However, to date there has been little quantitative research into bus operator separation dynamics. To better understand these dynamics, a hierarchical survival model was used to quantify monthly probability of separation for individual bus operators, based on a sample of two-year work histories for over 1300 bus operators employed by Metro Transit (Minneapolis–St. Paul, MN). Characteristics of operators at hire, such as age, gender, and driving experience, as well as work history events such as absences, incidents, and accidents, were used to understand what influences separation. Separation rate differed predictably with time, with the highest risk of both voluntary and involuntary separation in the first ten months of operator employment. Of bus operator characteristics at hire, prior commercial driving experience lowered the probability of separation. The number of absences from work, and accidents classified as the responsibility of the operator, increased the separation risk probability per month. The highest probability of separation was in operators hired without a commercial driver's license, whose work history included multiple accidents. Alterations to hiring and training practices may ameliorate risk of bus operator separation. Additionally, the hierarchical modeling approach utilized here has promise for predicting relative impacts of characteristics of employees and their work history on multiple aspects of employment.